Is a slow pulse-rate a reliable sign of digitalis toxicity? - Williams, P; Aronson, J; Sleight, P (1978)
64 of 910 hospital patients taking digoxin had a ventricular rate of less than 60 beats/min. In only 6 out of 57 of those investigated further could a diagnosis of digoxin toxicity be made on clinical, electrocardiographic, and biochemical grounds. No reason for the slow heart-rate could be found in 42 patients. Excessive vagal effects of digoxin in resting subjects may cause the bradycardia found in these in patients in the absence of digitalis toxicity.